Youth Sociolect in Uzbek (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article highlights several forms of sociolect, including slang and particularly the sociolect used by young individuals. Slangs are frequently employed, particularly in the speech of young individuals. Our study primarily focuses on elucidating the incorporation of the Uzbek language into the sociolect of young people, its promotion, and its significance in social communication.